Critical Thinking Ability of Senior High School Students in terms of Mathematical Self Efficacy in Project Based Learning with Project Assessment - Sa'adah, Daroinis; Masrukan, Masrukan; Mariani, Scolastika (Universitas Negeri Semarang, 2021)
This study has objectives to determine the effectiveness of project-based learning on critical thinking skills in terms of students 'mathematical self-efficacy and to find out critical thinking skills in terms of students' mathematical self-efficacy in project-based learning. This research was conducted at MAN 1 Semarang in academic year of 2019/2020. The researcher used mix methods with sequential explanatory. The research data were taken by means of questionnaires, observations, and tests then those were processed by completeness test, comparative test, influence test, and improvement test. The results showed that project-based learning was effective against critical thinking skills in terms of students' mathematical self-efficacy. Students with high mathematical self-efficacy have excellent critical thinking skills. Students with moderate ability in mathematical self-efficacy are having good critical thinking skills. Students with low mathematical self-efficacy have quite good critical thinking skills even though some of them did not achieved the minimum completeness criteria (KKM). The project-based learning model is suitable for improving students 'critical thinking skills in terms of students' mathematical self-efficacy with high, medium, and low dimensions with a different time allotment for each dimension.